An Assessment of the Civilian Acquisition Workforce Personnel Demonstration Project - Werber, Laura; Daugherty, Lindsay; Keating, Edward G.; Hoover, Matthew (RAND Corporation, 2023)
The U.S. Department of Defense (DoD) Civilian Acquisition Workforce Personnel Demonstration Project (AcqDemo) is an effort to reengineer the civilian personnel system to meet the needs of the acquisition workforce and to facilitate the fulfillment of the DoD acquisition mission. Congress required an independent assessment of the program against 12 criteria by September 30, 2012. This report is that legislatively mandated assessment.